Trends in Operative Treatment of Pediatric and Adolescent Forearm Fractures Among American Board of Orthopaedic Surgery Part II Candidates. Issue 8 (September 2021) - Testa, Edward J.; Medina Pérez, Giancarlo; Tran, Megan M.; Gao, Burke; Cruz, Aristides I.
Abstract : Background: Pediatric and adolescent forearm fractures are among the most common injuries treated by orthopaedic surgeons. Recent literature shows that there has been an increased interest in operative management for these injuries. The purpose of the current study was to examine the trends in case volume, patient age, surgeon fellowship training, and postoperative complications of surgically treated pediatric forearm fractures over >15-year period of American Board of Orthopaedic Surgery (ABOS) Part II Oral Examination candidates. Methods: ABOS Part II candidates' Oral Examination Case List data from 2003 to 2019 was queried for all pediatric and adolescent (19 y of age and below) forearm fractures treated operatively. Patient demographics, fracture type, complications, and candidate fellowship type were identified for each case. Linear regression was used to delineate annual trends in patient age, complication rates, and case volume by fellowship type. Analysis of variance was performed to evaluate complication rates by fellowship type. Statistical significance for all comparative analyses was set at P -value <0.05. Results: A total of 4178 pediatric and adolescent forearm fractures (mean age: 12.6 y; SD: 3.7 y) were treated surgically among ABOS Part II Oral Examination candidates during their 6-month collection periods from 2003 to 2019. The mean patient age decreased significantly ( P <0.001) over the study timeframe, while complication rates increased ( P <0.001). Pediatric fellowship-trained orthopaedic surgeons performed significantly more cases than general orthopaedic surgeons over recent years ( P <0.001). No significant trends were identified between fellowship type and complication rates. The overall surgical complication rate was 17%. The complication rate of open fractures was 24%, which was significantly >15% complication rate of closed fractures ( P <0.001). Conclusions: Fellowship-trained pediatric orthopaedic surgeons are performing an increasing number of pediatric and adolescent forearm fracture fixation when compared with other orthopaedic surgeons. The mean age of surgically managed pediatric forearm fracture patients has decreased from 2003 to 2019. There has been an increase in the rate of overall reported complications following pediatric forearm fracture surgery over recent years, without any significant association to any particular subspecialty. Future studies should evaluate the comparative effectiveness of surgical treatment of pediatric forearm fractures compared with closed management. Abstract : Supplemental Digital Content is available in the text.